Notes on Oriental and East Palaearctic Manota Williston (Diptera, Mycetophilidae), with the description of seven new species - Hippa, Heikki; Saigusa, Toyohei (Zootaxa, 2016)
The following new species of Manota are described: M. adunca (Taiwan), M. incilis (Nepal), M. integra (China), M. mitrata (China), M. nepalensis (Nepal), M. tayal (Taiwan) and M. vesca (Philippines). New records of the following species are given: M. acutangula Hippa (China, Taiwan), M. curvistylus Hippa, Kjærandsen and Saigusa (China), M. oblonga Hippa (China), M. perlobata Hippa (China) and M. planilobata Hippa (China). Characters of the Chinese material of M. curvistylus are discussed and drawings of the hypopygium of a Chinese specimen are given.